2008
DOI: 10.1016/j.ijantimicag.2007.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of prostatitis

Abstract: Background-Prostatitis describes a combination of infectious diseases (acute and chronic bacterial prostatitis), chronic pelvic pain syndrome, and asymptomatic inflammation.Materials and methods-We employed evidence-based methods to review the epidemiology of prostatitis syndromes.Results-The prevalence of prostatitis symptoms could be compared in five studies surveying 10 617 men. Overall, 873 participants met various criteria for prostatitis, representing an overall rate of 8.2%, with prevalence ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
169
3
24

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(205 citation statements)
references
References 28 publications
9
169
3
24
Order By: Relevance
“…The analyses of more than 12 000 men confirm other studies [2] which demonstrate that CP represents a large problem in adult male populations. Even the numbers that are seen in urology clinics may under represent the true magnitude of these symptom profiles that are observed.…”
supporting
confidence: 86%
“…The analyses of more than 12 000 men confirm other studies [2] which demonstrate that CP represents a large problem in adult male populations. Even the numbers that are seen in urology clinics may under represent the true magnitude of these symptom profiles that are observed.…”
supporting
confidence: 86%
“…Based on a population of >10 600 participants, a systematic review found an 8.2% prevalence of prostatitis symptoms [1].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies report that the prevalence of prostatitis-like symptoms is approximately similar to diabetes mellitus and ischemic heart disease. The rate of prostatitis-like symptoms was reported to range from 2.2% to 9.7%, and mean prevalence was 8.2% [1].…”
Section: Introductionmentioning
confidence: 99%